2003
DOI: 10.1177/0885066603255683
|View full text |Cite
|
Sign up to set email alerts
|

Industry-Sponsored Economic Studies in Critical and Intensive Care Versus Studies Sponsored by Nonprofit Organizations

Abstract: The purpose of this analysis of health economic studies in the field of intensive and critical care was to investigate whether any relationship could be established between type of sponsorship and (1) type of economic analysis, (2) health technology assessed, (3) sensitivity analysis performed, (4) publication status, and (5) qualitative cost assessment. Using the terms critical care or intensive care, all health economics publications in the field of critical and intensive care were identified in the Health E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…In another study in the field of oncology, Friedberg et al [38] found that, in 44 identified articles, industry sponsorship was more likely to report positive results. [39] Baker et al [40] studied 46 economic evaluations of antidepressants and found a clear relationship between study sponsorship and reporting of positive outcomes. [39] Baker et al [40] studied 46 economic evaluations of antidepressants and found a clear relationship between study sponsorship and reporting of positive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In another study in the field of oncology, Friedberg et al [38] found that, in 44 identified articles, industry sponsorship was more likely to report positive results. [39] Baker et al [40] studied 46 economic evaluations of antidepressants and found a clear relationship between study sponsorship and reporting of positive outcomes. [39] Baker et al [40] studied 46 economic evaluations of antidepressants and found a clear relationship between study sponsorship and reporting of positive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has consistently shown that industry-funded economic evaluations were more likely to report favourable cost effectiveness results to the sponsor. 1 2 3 4 5 6 7 8 9 10 Most of the published studies, however, were limited to specific diseases or treatments—for example, cancer, 2 6 7 9 10 antidepressants, 3 herpes zoster vaccine, 5 and statins. 4 The most recent analysis of bias in cost effectiveness studies based on systematic literature review was published more than 15 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…Industry’s economic ties to insurance coverage approval could lead to sponsorship bias in CEAs. Evidence has consistently shown that industry-funded economic evaluations were more likely to report favourable cost effectiveness results to the sponsor 12345678910. Most of the published studies, however, were limited to specific diseases or treatments—for example, cancer,267910 antidepressants,3 herpes zoster vaccine,5 and statins 4.…”
Section: Introductionmentioning
confidence: 99%